2020
DOI: 10.33448/rsd-v9i10.8424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoemulsion and essential oil from the leaves of Ocotea elegans against Dysdercus peruvianus

Abstract: The Dysdercus peruvianus Guérin-Méneville is commonly known as the cotton stainer bug. In this study, it was evaluated the insecticide activity and mode of action of the essential oil from leaves of Ocotea elegans Mez and its nanoemulsion against D. peruvianus. Leaves of O. elegans were extracted by hydrodistillation. The essential oil obtained was analyzed by gas chromatography coupled with electron impact mass spectrometry and flame ionization detector. The essential oil toxicity measured by lethal dose 50 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The essential oil from the leaves of O. indecora showed approximately 86% of sesquirosefuran, corroborating with the O. indecora chemical profile and sesquirosefuran amount (88-92%) described previously by other authors [29,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The essential oil from the leaves of O. indecora showed approximately 86% of sesquirosefuran, corroborating with the O. indecora chemical profile and sesquirosefuran amount (88-92%) described previously by other authors [29,31].…”
Section: Discussionsupporting
confidence: 91%
“…The sesquirosefuran has few reports about the molecule bioactivity, mainly insecticide activity [29,31], and none related to its antifungal potential. Sesquiterpenes and furanosesquiterpenes, in turn, have several recognized activities, and among them, Marongiu et al [33] demonstrated activity against several Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoemulsion containing the EO from O. indecora were active on D. peruvianus adult, a Hemiptera cotton pest, presenting a LD 50 equal to 162.18 µg/mL, with a sesquirosefuran oil concentration of 92 % (Nascimento et al, 2020). The leaves EO from the species Myrciaria floribunda was also effective against this pest with LC 50 values (µg/insect) equal to 309.64 after one day of treatment, and 94.42 after 22 days of treatment.…”
Section: Dysdercus Peruvianusmentioning
confidence: 98%